The Impact of Climate Risk on Credit Risk Parameters. Evidence from Five EU Economies - Białek-Szkudlarek, Martyna; Starosta, Wojciech (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
Increasingly frequent extreme weather events, leading to rising climate risk, are one of the key aspects that financial institutions presently analyse. This paper highlights the connection between climate risk indicators and two main drivers of the traditional risk management process: default rates and loss rates. This information is valuable to financial institutions, enabling them to manage climate change risks more effectively. The study fills a scientific gap by using new indicators to analyse the impact of climate risk on credit risk in the largest EU economies. We show the results for the five biggest European Union economies (Germany, Spain, Italy, the Netherlands, and France). We demonstrate strong, moderate, and weak connections for each pair of climate risk drivers and risk parameters using three correlation measures: Pearson, Spearman, and Kendall-Tau. Significant differences are observed between countries, with the highest number of correlated variables in the Netherlands. A high correlation is also observed in France and Italy, while the correlations in Spain and Germany are less pronounced. The correlations also vary by asset class, highlighting the need for a case-by-case approach to climate risk assessment.